Humanity on the Brink - Youth in Poland and Germany about Refugee Rights - Ziebertz, prof. dr dr Hans-Georg (Horyzonty Wychowania, 2020)
RESEARCH OBJECTIVE: The purpose of the presented paper, which has empirical nature, is to obtain data on how the rights of refugees are perceived today.THE RESEARCH PROBLEM AND METHODS: The research problem of the paper is: How do youth in Germany and Poland evaluate refugee rights and what factors influence their attitude towards refugee rights? The survey method was used in the research. The data collection took place 2013/2014. In Germany, the survey included a total of 2157 students, in Poland 1211 respondents.THE PROCESS OF ARGUMENTATION: The study was based on the assumption that attitudes towards refugee rights are predicted by such factors as: human dignity, empathy, religious beliefs, and socio-political perceptions and convictions. Based on these determinants, a conceptual model was created and used in the research.RESEARCH RESULTS: The findings show that respondents differ regarding refugee rights. German youth show some support for refugee rights and Polish youth are ambivalent. The strongest predictor for support of refugee rights for both groups is the concept of multiculturalism. The capacity for empathy and an advocacy of a politically active Christianity are important predictors, but only for the German sample.CONCLUSIONS, INNOVATIONS, AND RECOMMENDATIONS: The fact that religious beliefs have hardly positive impact on the support of refugee rights is a desideratum for religious education.